Pemanfaatan Teknologi Pendidikan dalam Pembelajaran Akidah Akhlak; Kajian Integratif Gerakan Pendidikan KH. Ahmad Dahlan dalam Film Sang Pencerah - Anisa Nuraida Rahmah; Unik Hanifah Salsabila; Muhammad Hafizh Hanafi (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
This paper aims to provide an overview of the use of educational technology in learning akidah akhlak as subject. This study uses a type of qualitative research with the semiotic analysis method by examining the figure of KH. Ahmad Dahlan in the film 'Sang Pencerah'. The result of this research is the strengthening of technology by utilizing the media has long been exemplified by KH. Ahmad Dahlan. Therefore, the use of technology in learning is not new and has strong historical roots as the da'wah strategy that KH has carried out. Ahmad Dahlan in broadcasting Islamic teachings. The implication is that Islam and technology should not be contradicted but should be further harmonized. If the era of KH. Ahmad Dahlan has been balancing it for a long time, so this era should move, namely by being a consumer of technology and starting as a producer because teaching Islam cannot be separated from the use of technology in the learning process.